SMAD2 is essential for TGF beta-mediated Th17 cell generation. - Malhotra, N; Robertson, E; Kang, J (2010)
TGFβ is the quintessential cytokine of T cell homeostasis. TGFβ signaling is required for the efficient differentiation and maintenance of CD4(+)FOXP3(+) T cells that inhibit immune responses. Conversely, in conjunction with the inflammatory cytokine IL-6, TGFβ promotes Th17 cell differentiation. The mechanism by which TGFβ signals synergize with IL-6 to generate inflammatory versus immunosuppressive T cell subsets is unclear. TGFβ signaling activates receptor SMADs, SMAD2 and SMAD3, which associate with a variety of nuclear factors to regulate gene transcription. Defining relative contributions of distinct SMAD molecules for CD4 T cell differentiation is critical for mapping the versatile intracellular TGFβ-signaling pathways that tailor TGFβ activities to the state of host interaction with pathogens. We show here that SMAD2 is essential for Th17 cell differentiation and that it acts in part by modulating the expression of IL-6R on T cells. Although mice lacking SMAD2 specifically in T cells do not develop spontaneous lymphoproliferative autoimmunity, Smad2-deficient T cells are impaired in their response to TGFβ in vitro and in vivo, and they are more pathogenic than controls when transferred into lymphopenic mice. These results demonstrate that SMAD2 is uniquely essential for TGFβ signaling in CD4(+) T effector cell differentiation.